2011
DOI: 10.1161/circulationaha.110.011734
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor–Like Domain 7 Is a Novel Inhibitor of Neutrophil Adhesion to Coronary Artery Endothelial Cells Injured by Calcineurin Inhibition

Abstract: Background— We investigated the effect of epidermal growth factor–like domain 7 (Egfl7) on nuclear factor-κB activation, intercellular adhesion molecule-1 expression, and neutrophil adhesion to human coronary artery endothelial cells after calcineurin-inhibition–induced injury. Methods and Results— Human coronary endothelial cells were incubated with cyclosporine (CyA) 10 μg/mL with or without Egfl7 (100 ng/mL) or the Notch receptor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…61 Specifically, Egfl7 overexpression in breast and lung carcinoma cells enhances tumor progression in immunocompetent mice and appears to do so by reducing the expression of tumor endothelial leukocyte adhesion molecules, including ICAM-1 and VCAM-1, thus preventing host immune cell infiltration. 61 The repression of ICAM-1 expression by EGFL7 is in keeping with observations made during endothelial cell injury 33,35 and highlights a possible novel mechanism by which EGFL7 promotes tumorigenesis.…”
Section: Egfl7 and The Notch Signaling Pathwaysupporting
confidence: 67%
See 2 more Smart Citations
“…61 Specifically, Egfl7 overexpression in breast and lung carcinoma cells enhances tumor progression in immunocompetent mice and appears to do so by reducing the expression of tumor endothelial leukocyte adhesion molecules, including ICAM-1 and VCAM-1, thus preventing host immune cell infiltration. 61 The repression of ICAM-1 expression by EGFL7 is in keeping with observations made during endothelial cell injury 33,35 and highlights a possible novel mechanism by which EGFL7 promotes tumorigenesis.…”
Section: Egfl7 and The Notch Signaling Pathwaysupporting
confidence: 67%
“…34 EGFL7 may also stimulate vascular regeneration by repressing key steps in the inflammatory activation of endothelial cells. 33,35 Specifically, it has been shown that EGFL7 represses NFB activation and the subsequent expression of ICAM-1 in response to hypoxia/reoxygenationinduced and calcineurin inhibition-induced endothelial injury. 33,35 In contrast to hypoxic conditions, EGFL7 expression is inhibited after hyperoxic exposure in both neonatal lungs in vivo and in endothelial cells in vitro, and reduced levels are associated with endothelial cell death.…”
Section: Egfl7 In Vascular Injury and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Badiwala et al (10) reported that treating human coronary artery endothelial cells stimulated by cyclosporin A or tacrolimus with exogenously added recombinant Egfl7 repressed neutrophil adhesion to these cells, decreased NF-B DNA-binding, and lowered ICAM-1 expression. We had also reported earlier that an Egfl7-producing tumor cell-conditioned medium prevented the adhesion of T-cells to the endothelial cells (7).…”
Section: Egfl7 Regulates Endothelial Activation During Inflammationmentioning
confidence: 99%
“…Indeed while CNIs can prevent acute rejection very effectively, they do not seem to have any significant effect on the prevention of CAV [10] , indicating that CAV is mediated via some pathways not modulated via the calcineurin pathway Badiwala et al [61] demonstrated that CsA induces injuries by increasing ICAM-1 expression on human coronary artery endothelial cells, thus promoting neutrophil adhesion. This effect could ultimately increase local cardiac inflammation and consequently facilitate the development of CAV.…”
Section: Impact Of Immunosuppressive Regimens On Cavmentioning
confidence: 99%